China Satellite Navigation Conference (CSNC) 2012 Proceedings - Sun, Jiadong; Liu, Jingnan; Yang, Yuanxi; Fan, Shiwei; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg, 2012)
Proceedings of the 3rd China Satellite Navigation Conference (CSNC2012) presents selected research papers from CSNC2012, held on 15-19 May in Guanzhou, China. These papers discuss the technologies and applications of the Global Navigation Satellite System (GNSS), and the latest progress made in the China BeiDou system especially. They are divided into 9 topics to match the corresponding sessions in CSNC2012, which broadly covered key topics in GNSS. Readers can learn about the BeiDou system and keep abreast of the latest advances in GNSS techniques and applications. SUN Jiadong is the Chief Designer of the Compass/BeiDou system, and the Academician of Chinese Academy of Sciences; LIU Jingnan is a professor at Wuhan University, and the Academician of Chinese Academy of Engineering; YANG Yuanxi is a professor at China National Administration of GNSS and Applications, and the Academician of Chinese Academy of Sciences; FAN Shiwei öis a researcher on satellite navigation.
VOL I: BeiDou/GNSS Navigation Application -- Satellite Navigation Model and Method -- Integrated Navigation and New Methods. VOL II: Satellite Navigation Signal System, Compatibility & Interoperability -- Precise Orbit Determination and Positioning -- Atomic Clock Technique and Time-Frequency System. VOL III: Satellite Navigation Augmentation and Integrity Monitoring -- BeiDou/GNSS Test and Evaluation Technology -- BeiDou/GNSS User Terminal Technology.
Keywords: Engineering; Physical geography; Astronautics; Telecommunication; Engineering; Aerospace Technology and Astronautics; Communications Engineering, Networks; Astronomy, Observations and Techniques; Geophysics/Geodesy.